Synthesis, Characterization, ADME Study and Antimicrobial Evaluation of New 1,2,3-triazole Derivatives of 2-phenyl benzimidazole. - Asmaa Adnan Abdulnabi; Karima Fadhil Ali; Basma M.Abd Razik (College of Pharmacy / Mustansiriyah University, 2023)
Novel 2-amino benzimidazole derivatives containing amide, azide and 1,2,3-triazole moieties have been synthesized. Compound 3 was synthesized by reaction of o-phenylenediamine with p-aminobenzoic acid. Compound 3 was converted into amide by treatment with chloroacetyl chloride to get compound 4. Compound 4 and sodium azide were combined to create compound which has an azide group. Compound 5 was converted into 1,2,3-triazole derivatives by treatment with acetylene derivatives. FTIR, 1H-NMR, and Mass spectra have been used to confirm the chemical structures of various substances. By using a technique called well diffusion agar, the final products were examined in vitro to predict activity against two kinds of gram-positive bacteria and two kinds of gram-negative bacteria as well as the antifungal activity against Candida albicans fungus. All the final products exhibited moderate to potent activity compared to Trimethoprim and Fluconazole as reference antibacterial and antifungal drugs respectively. Swiss ADME was also used to undertake ADME tests to determine the bioavailability, drug-likeness and topological polar surface area of the synthesized molecule. The results showed that every chemical tested was absorbed orally and followed the Lipinski rule.